The role of early intergroup experiences for identification with all humanity in adulthood - Hamer, Katarzyna; McFarland, Sam (Frontiers in Psychology, 2023)
Identification with all humanity (IWAH), defined as a bond with and concern for people all over the world, predicts concern for global problems, commitment to human rights, and prosocial activities. However, it is still unknown how such a broad social identification develops and if early experiences play any role. Two studies explored the role of diverse childhood and adolescence intergroup experiences in predicting IWAH in adulthood. We focused on experiences such as being raised in diversity and having intergroup friends, helping or being helped by various others, and having experiences leading to re- or de-categorization, and introduced a new Childhood/Adolescent Intergroup Experiences (CAIE) scale. Study 1 (N = 313 U.S. students, Mage = 21) and Study 2 (N = 1,000, a representative Polish sample, Mage = 47) found that this kind of intergroup experiences during childhood and adolescence predicted IWAH beyond the effects of its other known predictors, such as empathy, openness to experience, universalism, right-wing authoritarianism, social dominance orientation or ethnocentrism. These results, obtained on various samples and in countries with different ethno-cultural contexts, point to potential ways of enlarging IWAH during childhood and adolescence.